An Approach Of Crystal Engineering For Solubility Enhancement Of Poorly Water-Soluble Drugs - Mr. Devendra Singh, Ms. Rojalini Samanta (Drugs and Cell Therapies in Hematology, 2021)
As a result of intermolecular interactions, crystal engineering involves the synthesis of novel structures and properties in medicinal molecules. For more than 40 percent of newly designed medicines, low solubility and low bioavailability have hampered their clinical implementation.Cocrystallzation is a bicomponent system in which bonds are formed between drug and coformer, improving the solubility and flow properties of weakly water-soluble pharmaceuticals. It is important to note that cocrystallization has no effect on the drug’s chemical properties or biological efficacy. Implementing cocrystallization for solubility improvement has the added benefit of improving flow and compressibility.